Cytotoxicity and secondary metabolites production in terrestrial Nostoc strains, originating from different climatic/geographic regions and habitats: is their cytotoxicity environmentally dependent? - Hrouzek, Pavel; Tomek, Petr; Lukešová, Alena; Urban, Jan; Voloshko, Ludmila; Pushparaj, Benjamin; Ventura, Stefano; Lukavský, Jaromír; Stys, Dalibor; Kopecký, Jiří (Environmental toxicology, 2011)
Extensive selection of cyanobacterial strains (82 isolates) belonging to the genus Nostoc, isolated from different climatic regions and habitats, were screened for both their secondary metabolite content and their cytotoxic effects to mammalian cell lines. The overall occurrence of cytotoxicity was found to be 33%, which corresponds with previously published data. However, the frequency differs significantly among strains, which originate from different climatic regions and microsites (particular localities). A large fraction of intensely cytotoxic strains were found among symbiotic strains (60%) and temperate and continental climatic isolates (45%); compared with the less significant incidences in strains originating from cold regions (36%), deserts (14%), and tropical habitats (9%). The cytotoxic strains were not randomly distributed; microsites that clearly had a higher occurrence of cytotoxicity were observed. Apparently, certain natural conditions lead to the selection of cytotoxic strains, resulting in a high cytotoxicity occurrence, and vice versa. Moreover, in strains isolated from a particular microsite, the cytotoxic effects were caused by different compounds. This result supports our hypothesis for the environmental dependence of cytotoxicity. It also contradicts the hypothesis that clonality and lateral gene transfer could be the reason for this phenomenon. Enormous variability in the secondary metabolites was detected within the studied Nostoc extracts. According to their molecular masses, only 26% of these corresponded to any known structures; thus, pointing to the high potential for the use of many terrestrial cyanobacteria in both pharmacology and biotechnology.
Keywords: symbióza; Nostoc; Phylogeny; ekosystém; půdní mikrobiologie; druhová specificita; podnebí; Symbiosis; Climate; Soil Microbiology; Cytotoxins; Ecosystem; fylogeneze; Species Specificity; cytotoxiny